A novel benefit-oriented multi-objective optimization framework for efficiency, NOx, and H2S in coal-fired boilers - Cong Wang; Yiqing Yang; Bowen Lin; Jiaqi Ma; Jun Xu; Kai Xu; Long Jiang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Transfer learning model for coal lower heating value prediction with improved applicability to cross-sample datasets - Jiaqi Ma; Jun Xu; Cong Wang; Bowen Lin; Long Jiang; Kai Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (International Journal of Coal Geology, 2026)

Critical ventilation thresholds for hydrogen leakage of fuel cell vehicles in tunnels based on scaled experiment - Luming Yang; Jun Shen; Jianwei Li; Cong Yin; Qi Lin; Lei Shi (Tunnelling and Underground Space Technology, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

Fire performance and post-fire residual behavior of insulated CFRP shear-strengthened RC beams: An experimental and numerical study - Wan-Yang Gao; Jun-Cong Lin; Ke-Xu Hu; Jian Yang (Engineering Structures, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Energy-saving low-frequency vibration-assisted riveting process for joining high-strength metallic structures with enhanced performance - Cong Shao; Jun Lin; Congxiao Yu; Yanjin Guan; Liang Chen; Xiangshan Kong; Cunsheng Zhang; Guoqun Zhao (Journal of Cleaner Production, 2025)

Soil comammox Nitrospira dominates over ammonia-oxidizing archaea and bacteria in the invasion of Solidago canadensis - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Xiang-Zhen Li; Dao-Lin Du; Zhi-Cong Dai; Guang-Qian Ren; Xiao-Jun Zheng; Chao-Ying Liu (Plant and Soil, 2025)

Finding the perfect fit: Optimal Mn-ion site modification to improve the electrochemical performance of Ni/Co-free Mn-based layered oxide cathode toward potassium-ion batteries - Yicheng Lin; Shaohua Luo; Jun Cong; Zhaozhan Shi; Lixiong Qian; Shengxue Yan; Yahui Zhang (Chemical Engineering Journal, 2025)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Experimental investigation on the horizontal impact response of precast RC bridge piers with grouted sleeve connections considering defects - An He; Dun-Cong Zheng; Jian Cai; Qing-Jun Chen; Xu-Lin Tang; Jia-Bin Ye (Engineering Structures, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Electrolyte design to regulate the electrode–electrolyte interface on the electrochemical performance for K0.5MnO2||graphite-based potassium-ion batteries - Yicheng Lin; Shaohua Luo; Pengwei Li; Jian Feng; Wei Zhao; Jun Cong; Shengxue Yan (Chemical Engineering Journal, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Reliability analysis of core power optimization control using Kalman filter for accelerator driven system based on reconfigurable computing - Jin-Yang Li; Huan Lin; Long Gu; You-Peng Zhang; Jun-Liang Du; Yong-Quan Wang; Cong Lin; Xing-Chen Zhou; Tian Wang (Annals of Nuclear Energy, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Targeted next-generation sequencing improves diagnosis of hereditary spastic paraplegia in Chinese patients - Cong Lu; Li-Xi Li; Hai-Lin Dong; Qiao Wei; Zhi-Jun Liu; Wang Ni; Aaron D. Gitler; Zhi-Ying Wu (Journal of Molecular Medicine, 2018)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Optimization Studies on Prokaryotic Cell Expression of the Human Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) - Lin Hao; Zhi-Guo Zhang; Zheng-Duo Shi; Kun Pang; Jun-Jie Zhang; Yang Dong; Cong-Hui Han (Cell Biochemistry and Biophysics, 2015)

High-efficiency propagation of Chinese water chestnut [Eleocharis dulcis (Burm.f.) Trin. ex Hensch] using a temporary immersion bioreactor system - Meiping Gao; Wen Jiang; Shaolong Wei; Zhicheng Lin; Binghua Cai; Liu Yang; Cong Luo; Xinhua He; Jun Tan; Lijuan Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Gold complexes inhibit the aggregation of prion neuropeptides - Xuesong Wang; Lei He; Cong Zhao; Weihong Du; Jun Lin (JBIC Journal of Biological Inorganic Chemistry, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Analysis of Na+/Ca2+ exchanger (NCX) function and current in murine cardiac myocytes during heart failure - Lin Xu; Jing Chen; Xu-Yong Li; Shan Ren; Cong-Xin Huang; Gang Wu; Xiao-Yan Li; Xue-Jun Jiang (Molecular Biology Reports, 2012)

Cross-talk between NMDA and GABAA receptors in cultured neurons of the rat inferior colliculus - DanNi Cong; ZhengQuan Tang; LongZhu Li; YiNa Huang; Jun Wang; Lin Chen (Science China Life Sciences, 2011)

Role of microRNA-21 and effect on PTEN in Kazakh’s esophageal squamous cell carcinoma - Wen-jing Ma; Guo-dong Lv; Aerziguli Tuersun; Qing Liu; Hui Liu; Shu-tao Zheng; Cong-gai Huang; Jun-guo Feng; Xing Wang; Ren-yong Lin; Ilyar Sheyhidin; Xiao-mei Lu (Molecular Biology Reports, 2011)

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Conversion of trypsin into a selenium-containing enzyme by using chemical mutation - Jun-Qiu Liu; Ming-Shou Jiang; Gui-Min Luo; Gang-Lin Yan; Jia-Cong Shen (Biotechnology Letters, 1998)